2018
DOI: 10.1111/mmi.14117
|View full text |Cite
|
Sign up to set email alerts
|

The actinobacterial WhiB‐like (Wbl) family of transcription factors

Abstract: SummaryThe WhiB‐like (Wbl) family of proteins are exclusively found in Actinobacteria. Wbls have been shown to play key roles in virulence and antibiotic resistance in Mycobacteria and Corynebacteria, reflecting their importance during infection by the human pathogens Mycobacterium tuberculosis, Mycobacterium leprae and Corynebacterium diphtheriae. In the antibiotic‐producing Streptomyces, several Wbls have important roles in the regulation of morphological differentiation, including WhiB, a protein that contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
79
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(82 citation statements)
references
References 86 publications
(180 reference statements)
3
79
0
Order By: Relevance
“…Our results showed that AdpA Sx negatively affects cell growth and morphological differentiation in S. xiamenensis 318. Electrophoretic mobility shift assays (EMSAs) were therefore performed on several putative AdpA Sx targets involved in cell growth and morphological differentiation: ssgA (sxim_03860), encoding a putative membrane protein homologous to ssgB of Streptomyces coelicolor (31); ftsZ (sxim_10220), encoding a putative cell division protein; ftsH (sxim_23050), encoding a putative cell division GTPase; amfC (sxim_30820), encoding an aerial mycelium-associated protein (32); sxim_18210 (whiB), sxim_19730 (wblA1), sxim_24890 (wblA2), and sxim_39910 (wblE), encoding WhiB-family proteins that regulate morphological differentiation (33,34); sxim_29740, encoding a sporulation-associated protein; bldA, encoding a UUA-reading tRNA-leucine (21); bldD (sxim_03450), encoding a pleiotropic negative regulator of morphological and physiological development; and bldG (sxim_41700), encoding an anti-antisigma factor homolog to BldG, which controls key developmental processes in S. coelicolor and S. griseus (35,36).…”
Section: Resultsmentioning
confidence: 99%
“…Our results showed that AdpA Sx negatively affects cell growth and morphological differentiation in S. xiamenensis 318. Electrophoretic mobility shift assays (EMSAs) were therefore performed on several putative AdpA Sx targets involved in cell growth and morphological differentiation: ssgA (sxim_03860), encoding a putative membrane protein homologous to ssgB of Streptomyces coelicolor (31); ftsZ (sxim_10220), encoding a putative cell division protein; ftsH (sxim_23050), encoding a putative cell division GTPase; amfC (sxim_30820), encoding an aerial mycelium-associated protein (32); sxim_18210 (whiB), sxim_19730 (wblA1), sxim_24890 (wblA2), and sxim_39910 (wblE), encoding WhiB-family proteins that regulate morphological differentiation (33,34); sxim_29740, encoding a sporulation-associated protein; bldA, encoding a UUA-reading tRNA-leucine (21); bldD (sxim_03450), encoding a pleiotropic negative regulator of morphological and physiological development; and bldG (sxim_41700), encoding an anti-antisigma factor homolog to BldG, which controls key developmental processes in S. coelicolor and S. griseus (35,36).…”
Section: Resultsmentioning
confidence: 99%
“…The same study showed that it forms a stable complex with the sigma factor SigA that is dependent on the cluster; reaction with NO led to dissociation of the complex and a form of WhiB1 that can bind its own promoter . Other M. tuberculosis Wbl proteins have been shown to interact with SigA, suggesting that Wbl proteins commonly function together with partner proteins …”
Section: Introductionmentioning
confidence: 95%
“…[7,14] Other M. tuberculosis Wbl proteins have been shown to interactw ith SigA, suggesting that Wbl proteins commonly function together with partner proteins. [15] The mechanismsb yw hich Fe-S regulatory proteins react with NO are not well characterized. Recent advances in techniques for Fe-S protein preparation and handling have facilitated studies by av ariety of methods that have demonstrated that multinuclear iron species similar to the well known inorganic complexes Roussin's Red Ester (RRE;[ Fe 2 (NO) 4 (SR) 2 ]) and Roussin's Black Salt (RBS;[ Fe 4 (NO) 7 (S) 3 ]) [16] (see Figure S1) are major products.…”
Section: Introductionmentioning
confidence: 99%
“…Such gene-family expansions are well known in streptomycete regulatory genes [7][8][9][10] and in specialized metabolite biosynthesis [11,12]. Yet, there has been limited attention focussed on the genes of central metabolism despite a number of gene-expansion events being identified from biochemical and phylogenomic studies.…”
Section: Introductionmentioning
confidence: 99%